(untitled) (Per Musi, 2017)
Giambattista Marino’s (1569-1625) poems were set to music by many composers during the first half of the 17th century. His epigrammatic style, using witty jokes, rhetorical devices, erotic conceits and various kinds of baroque ornaments, was both imitated and criticized in his own time, later underestimated and condemned as a period of decline in the history of Italian poetry. More recently, literary historians have reassessed his status, but musicians and musicologists have been slow in following their example. Poems are made intensely "pathetic", by means of sudden changes, unexpected metaphors, complex and uncommon rhetorical figures. Composers at the beginning of the 17th century were looking exactly for that: to reduce the whole madrigal (or other vocal genres) into a few concise textual-musical ideas (using the technique of contrast, like painters were doing with the chiaroscuro), fitting the ideal of expressing affetti and producing meraviglia. To which extent did composers accept and exploit this new language and what does it imply? What are the changes in their choices in the transition from the canonical madrigal towards the modern monody? How is the original potential of the poem conveyed or dispersed when it is set to music? These questions will be the central issues of this paper.